Comments on “A preliminary study on a Mirror of Japan (Ri ben yi jian)” - Yi Yang (Trans/Form/Ação)
Commented Article: TONG, Jie; MA, Ji. A preliminary study on A Mirror of Japan (Ribenyijian). Trans/Form/Ação: Unesp journal of philosophy, v. 45, n. 4, p. 117-136, 2022.